2023
DOI: 10.3389/fpls.2023.1140267
|View full text |Cite
|
Sign up to set email alerts
|

Individual and combined effects of arbuscular mycorrhizal fungi and phytohormones on the growth and physiobiochemical characteristics of tea cutting seedlings

Abstract: Both arbuscular mycorrhizal fungi (AMF) and phytohormones collectively regulate plant growth and root development, but their individual and combined effects on tea [Camellia sinensis (L.) O. Kuntze] cutting seedings remain unclear. This study examined the individual and combined effects of two species of AMF (Rhizophagus intraradices, RI and Funneliformis mosseae, FM) and two types of palnt hormones (strigolactones, SLs; polyamines, PAs) on tea cutting seedings, by evaluating the growth and physiobiochemical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 71 publications
0
5
0
5
Order By: Relevance
“…Under saline-alkali stress (SS), root infection rate, spore density and mycelium length were significantly decreased under BR treatment this resulted in better uptakes of both water and nutrients and resulting in considerable increase in growth and biomass production. Previous studies have shown that plant hormones are important factors affecting the development of AM fungi in the process of symbiosis (Liao et al, 2016;Cao et al, 2021;Gao et al, 2023).…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%
“…Under saline-alkali stress (SS), root infection rate, spore density and mycelium length were significantly decreased under BR treatment this resulted in better uptakes of both water and nutrients and resulting in considerable increase in growth and biomass production. Previous studies have shown that plant hormones are important factors affecting the development of AM fungi in the process of symbiosis (Liao et al, 2016;Cao et al, 2021;Gao et al, 2023).…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%
“…MHB juga diketahui menghasilkan beberapa senyawa volatil maupun non volatil seperti CO2, tiamin dan 2-methylisoborneol yang meregulasi germinasi spora (Nasslahsen et al, 2022;Guarnizo et al, 2023). Namun demikian informasi tentang pengujian kemampuan FMA maupun MHB untuk meningkatkan pertumbuhan bibit kentang secara in vitro dalam menghasilkan hormon, asam organik maupun enzim masih terbatas (Minemba et al, 2019).…”
Section: Selanjutnyaunclassified
“…Inokulasi MHB diberikan dengan cara meneteskan 3 mL larutan kultur menggunakan pipet ke dalam tabung (Nurbaity et al, 2016) Adanya hormon tumbuh terutama giberelin yang dihasilkan oleh MHB yang cukup tinggi memperkuat hasil-hasil penelitian sebelumnya yang memperlihatkan bahwa salah satu mekanisme peningkatan metabolisme mikroba dan tanaman yang diberi MHB karena adanya hormon tumbuh yang dihasilkan (Fritz et al, 2022). Giberelin merupakan senyawa organik yang berperan dalam proses perkecambahan karena dapat mengaktifkan reaksi enzimatik di dalam benih sehingga metabolisme sel meningkat (Gao et al, 2023).…”
Section: Rancangan Percobaanunclassified
See 2 more Smart Citations